Currency substitution: Evidence from Nigeria - Sani I. Doguwa (CBN Journal of Applied Statistics, 2014)
This paper examines the existence, causes and effects of currency substitution in Nigeria by estimating conventional money demand equations based on a partial adjustment and an autoregressive distributed lag models using three definitions of monetary aggregates. The behavior of the foreign currency/Naira deposit ratios have been influenced by devaluation expectations, exchange rate risks and political uncertainties during the Yar'adua-Jonathan presidency. Also, the money demand estimations reveal that short-term foreign interest rates significantly affect the demand for the Naira, suggesting strong evidence of currency substitution and the possibility of importing considerable instability in the economy.
Keywords: E51; E41; C22; 330; Currency Substitution; Demand for Money Function; Autoregressive Distributed Lag Approach; Monetary Policy